GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, MOTIVASI DAN KINERJA PENDIDIK SMK NEGERI DI LOMBOK TIMUR - Muhardi, Muhardi; Muawanah, Umi; Farhan, Djuni (Universitas Hamzanwadi, 2023)
This study was meant 1) to partially analyze the influence of leadership style, organizational culture and motivation on the performance of Educators in State Vocational High Schools in East Lombok Regency. 2) to analyze whether the variables of leadership style, organizational culture and motivation simultaneously influence the performance of Educators in State Vocational High Schools in East Lombok Regency. 3) to analyze the variables of leadership style, organizational culture and motivation, which variables had the most dominant influence on the performance of Educators in State Vocational High Schools in East Lombok Regency. This study was a causal associative research. This study was also a population research where the respondents who returned the questionnaire were 78 respondents. Quantitative analysis technique was used in this study along with the assistance of the SPSS 20 aplication. It showed that 1) Leadership Style had a positive influence on the performance of educators. 2) Organizational culture had a positive influence on the performance of educators but was not significant. 3) Motivation had a positive influence on the performance of educators. 4) Leadership Style, Organizational Culture and Motivation simultaneously influence on the Performance of Educators. 5) Among the three independent variables, motivation variable had the most dominant influence in improving the performance of Educators in State Vocational High Schools in East Lombok Regency.